Ribbon dance - Lee, Sharon, 1952-; Miller, Steve, 1950- (Lee, Sharon, 1952- Liaden universe, 2025)
"On a world where cake is a necessity, it takes the Grid to protect the civilized and the deaf from the dire influences of the ambient and to keep the chaotic Haosa at bay.Having arrived at recently Dust-bound Colemeno, Trader Padi yos'Galan is essential to Master Trader Shan yos'Galan's plan to recoup Clan Korval's fortunes by establishing new routes for the clan's tradeship. Shan's inner Healer insists Padi come to terms with her as-yet unplumbed psychic abilities, which might place her in the top tier of dramliz, if she can learn control. Padi yearns to concentrate on trade, but Colemeno's fey ambient and deadly long-term politics combine to bring her face-to-face with the Haosa, and in particular with the mysterious and untouchable Tekelia, as Korval's trade mission's necessity of a port audit collide with a cruel history of murder, deception, and brutality. Amid the dangers, Padi unexpectedly finds herself eagerly exploring her dramliz side when faced with the unspoken powers of the ambient, the sky-filling energy of the ribbon dance, and Tekelia's mutable eyes."--